Peritoneal Carcinosis in Apparently Benign Cortisol Producing Adrenal Adenoma≥5 cm in Diameter: The Need of Regular Postoperative Surveillance - Brauckhoff, M.; Varhaug, J. E.; Hauptmann, S.; Akslen, L. A.; Thanh, P. N.; Viste, A.; Heie, A.; Dralle, H. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Clinical and histopathological distinction between benign and malignant adrenocortical tumors can be a challenge.Report on 2 patients with cortisol producing apparently benign adrenal adenomas≥5 cm in diameter with local malignant recurrence and peritoneal carcinomatosis after endoscopic surgery.Case 1: The 59-year-old male presented with adrenal hypercortisolism due to a 5.0 cm large adrenal tumor on the left side. A retroperitoneoscopic total adrenalectomy was performed. Histologically, a benign adrenal adenoma (Weiss score 1, Ki-67<2%) was found. 6 months later, the patient developed clinically and biochemically recurrent disease with recurrent tumor in the left adrenal region and peritoneal carcinomatosis. The patient died 5 months after second surgery.Case 2: The 32-year-old female was pregnant in 27th week when presenting with adrenal hypercortisolism due to a 5.5 cm large adrenal tumor on the left side. She was operated on using a laparoscopic approach and a total adrenalectomy was carried out. Histological examination revealed a benign adrenocortical adenoma (Weiss score 1, Ki-67<5%). 4 years later, the patient came back with clinically and biochemically recurrent disease. Imaging showed a 10 cm large tumor in the left retroperitoneum and a diffuse peritoneal carcinomatosis. The patient died 2 months after diagnosis.Cortisol producing adrenal tumors≥5 cm in diameter are at risk to be misdiagnosed as apparently benign. Regular surveillance should be considered in patients presenting with large cortisol producing tumors.
Keywords: adrenal cushing disease; malignant recurrence; postoperative surveillance